Environmental study on the effect of heavy metals on the life cycle of Some Odonata naiad in the north regions of Basrah, Iraq - Khader et al. (Iraqi Journal of Aquaculture, 2025)
An environmental study was conducted on Odonata in the waters of North Basrah from October 2020 to May 2024, to assess the relationship between environmental factors and pollutants. The study covered six aquatic stations and evaluated the density of Odonata naiads monthly. The results showed: - The highest numerical density of naiads was 5.28 naiads /6 draws in December and 4.52 naiads /6 draws in the Sharsh site. - The impact of trace elements on the population density of naiads, where a high inverse correlation was found between cadmium and population density in the city site (-0.969). - A good inverse relationship between copper and lead and population density in the Thaghr site (-0.982/-0.626). - The impact of trace elements on the age and number of molts of Odonata naiads in the laboratory, where a direct relationship was found between the concentration of cadmium, zinc, and nickel and the number of molts. The study provided valuable insights into the impact of pollutants on Odonata in the waters of North Basra and can contribute to the development of environmental protection strategies.